Hacia una educación superior de calidad: experiencia y perspectiva docente, desde un enfoque directivo (Memorias Sifored - Encuentros Educación UAN, 2023)
Quality higher education is essential for individual and collective development, economic growth, innovation, and the advancement of more just and advanced societies. The objective is to assess teaching performance and professionalism, considering the substantive functions (teaching, research, and social outreach) from an educational leadership perspective, with a focus on achieving high-quality higher education. The study followed a descriptive qualitative approach, of exploratory nature, and content analysis was conducted. The instrument used was a semi-structured interview comprising seven (7) questions that explored teaching performance and the teaching profession within the context of substantive functions. Findings underscore the importance of having a dedicated and highly qualified teaching staff that significantly contributes to the quality and educational excellence of university education.
Keywords: Teacher training; innovation; Higher education; pedagogical practices